การแสวงหาค่าเช่าทางเศรษฐกิจของนักการเมืองท้องถิ่น และธุรกิจรับเหมาก่อสร้าง - ลลิตชุ ฉันทธนไพบูลย์ (โรงเรียนนายร้อยพระจุลจอมเกล้า, 2022)
The objectives of this research, "Rent Seeking in Local Politicians and Construction Business" are 1) to study rent-seeking behaviors of local politicians and construction business and 2) to examine rent-seeking behaviors of local politicians and construction business as a result of changing from e-Auction to e-Bidding. This qualitative research verified by triangulation method and integrated collecting data sources by observing and interviewing. The research participants were divided into two groups. The first group consisted of 10 local politicians serving in the executive role, and the second group consisted of 10 construction contractors. From the study, it was found that most politicians did not come from political family. They had political network after starting political career. The changing of procurement had effects on finding the economic rent of local politicians and construction contractors. E-Auction first gave benefits to each other, but changing to e-Bidding led to the reduction in the portion of the benefits between contractors and local politicians. There were more new businessmen that dealt with construction, so it made alternative bidders. However, the problem was not solved by e-Bidding. Construction business still had an opportunity to get economic rent, but the way had been changed. The researcher therefore suggests further studies on whether or not anyone can find the benefit from such specific procurement.